The Monarchy Shapes Up: Arboreal Metaphors in Royal Propaganda and Court Panegyrics during the Reign of Louis XV. (7th September 2015) - Pacini, Giulia
Abstract: On 25 February 1745, during a ball celebrating the Dauphin's marriage to the Infanta of Spain, Louis XV dressed up as a pruned yew tree. A large watercolour and hundreds of prints produced by the royal office of the Menus Plaisirs offered contemporaries a stunning image of this event. This article analyses the self‐fashioning implicit in the king's sartorial choice, arguing that it informed a new political script characterised by an increasingly technical arboreal discourse. Royal epithalamia in particular drew on tree metaphors to describe the health of the body politic in the second half of the eighteenth century.